2006
DOI: 10.4049/jimmunol.177.10.6780
|View full text |Cite
|
Sign up to set email alerts
|

T Regulatory and Primed Uncommitted CD4 T Cells Express CD73, Which Suppresses Effector CD4 T Cells by Converting 5′-Adenosine Monophosphate to Adenosine

Abstract: CD73 (5′-ectonucleotidase) is expressed by two distinct mouse CD4 T cell populations: CD25+ (FoxP3+) T regulatory (Treg) cells that suppress T cell proliferation but do not secrete IL-2, and CD25− uncommitted primed precursor Th (Thpp) cells that secrete IL-2 but do not suppress in standard Treg suppressor assays. CD73 on both Treg and Thpp cells converted extracellular 5′-AMP to adenosine. Adenosine suppressed proliferation and cytokine secretion of Th1 and Th2 effector cells, even when target cells were acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
319
1
10

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 386 publications
(344 citation statements)
references
References 60 publications
14
319
1
10
Order By: Relevance
“…One of the suppressive mechanisms attributed to Treg cells is metabolic disruption, ascribed in part to the expression of CD39 and CD73 [11,59,60]. These ectonucleotidases act in concert to generate to hydrolyze ATP and ADP to adenosine.…”
Section: Discussionmentioning
confidence: 99%
“…One of the suppressive mechanisms attributed to Treg cells is metabolic disruption, ascribed in part to the expression of CD39 and CD73 [11,59,60]. These ectonucleotidases act in concert to generate to hydrolyze ATP and ADP to adenosine.…”
Section: Discussionmentioning
confidence: 99%
“…Tregs reduce eosinophil infiltration, Th2 cytokine production, and airway hyperreactivity (reviewed in [88,97]). ATP-degrading enzymes (CD39 and CD73) highly expressed on the membrane on Tregs are recognized recently as their activation markers [98,99]. Tregs exert immune suppression by increasing the concentration of intracellular cAMP in target cells [98].…”
Section: Purinergic Signaling In Allergic Airway Inflammation: Focus mentioning
confidence: 99%
“…Adenosine binding to A 2A R expressed by T cells suppresses their immunostimulatory activity. Kobie et al (2006) have shown that these FoxP3 + CD25 + CD4 + T regs express an extracellular 5′ectonucleotidase (CD73), which converts extracellular 5′-AMP to adenosine and suppresses T cell activity via binding to A 2A receptors on T cells [163]. have shown that FoxP3 + CD25 + CD4 + T regs also express CD39 ecto-ATPase/ADPase and CD73 ecto-5′nucleotidase, which shows involvement of these T regs in synthesis of extracellular adenosine [164].…”
Section: Adenosine and T Cellsmentioning
confidence: 99%
“…Primed uncommitted CD4 + T precursor Th (Thpp) cells and FoxP3 + CD25 + CD4 + T regs , produce immunosuppressive extracellular adenosine as both these cell types express CD73 (5′-ectonucleotidase), which has the potential to convert 5′adenosine monophosphate (5′-AMP) to adenosine [163]. Adenosine binding to A 2A R expressed by T cells suppresses their immunostimulatory activity.…”
Section: Adenosine and T Cellsmentioning
confidence: 99%